2011
DOI: 10.1007/dcr.0b013e3181fec4fd
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs Laparoscopic Resection of Rectal Cancer: Short-Term Outcomes of a Case-Control Study

Abstract: Robotic rectal cancer resection can be safely performed by experienced laparoscopic surgeons, with acceptable short-term outcomes comparable to those for laparoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 21 publications
9
138
2
Order By: Relevance
“…Additionally, RCS may offer an advantage in dissection in the deep pelvis especially in patients who have undergone pre-operative chemotherapy [2,9]. While each surgical method offers some advantages over the other, several studies have demonstrated comparable outcomes between robotic and laparoscopic colorectal surgery for intra-operative morbidity, complication rates, and postoperative recovery [1,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, RCS may offer an advantage in dissection in the deep pelvis especially in patients who have undergone pre-operative chemotherapy [2,9]. While each surgical method offers some advantages over the other, several studies have demonstrated comparable outcomes between robotic and laparoscopic colorectal surgery for intra-operative morbidity, complication rates, and postoperative recovery [1,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…169,170 Alongside this are decisions about how to undertake a particular operation with the robot, again a decision typically undertaken by the consultant surgeon and again not a one-off decision but one likely to evolve over time. For example, in robot-assisted rectal cancer surgery, there is no standardised technique and the decision has to be made whether to perform it as a hybrid operation or totally robot assisted.…”
Section: A Realist Review Of Stakeholders' Theoriesmentioning
confidence: 99%
“…171,176 Yet others pointed to a longer operative time, perceived as being due to collisions of the robotic arms, itself a consequence of lack of experience with proper positioning of the robotic ports. 169 It has also been argued that longer operation duration is related to the lack of tactile information, leading surgeons to move more slowly because they have to rely on visual information only. 177 However, one study found no difference in overall duration because, although the set-up time was significantly longer, this was balanced out by a significantly shorter operative time, which the authors argued was due to the technical advantages that the robot provides to the surgeon.…”
Section: A Realist Review Of Stakeholders' Theoriesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Prior studies have demonstrated that robotic surgery is feasible and safe 7,[11][12][13][14][15][16][17][18]20,21 but may be associated with higher cost and longer operative duration, particularly for rectal resections. 10,25 Given the single-centre reporting bias present in much of the literature, there is a need for research using multi-institutional data.…”
mentioning
confidence: 99%